Manajemen risiko rantai pasok kopi robusta (Green bean) organik desa Pasrujambe Kabupaten Lumajang - Annisa Choirun; Imam Santoso; Retno Astuti (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Organic coffee robusta is a leading commodity produced by farmers because it has a significant enough demand. Organic coffee robusta is sold as green beans or processed coffee roasted and ready to brew. Supply chain management is essential considering that agricultural commodities have perishable, seasonal, wide variety, and bulky limitations, thereby increasing the risk of supply chain activities. Complexity in the supply chain creates various risks that must be minimized and mitigated. This study aims to analyze the supply chain risk of organic robusta coffee and determine the risk mitigation strategy of the organic robusta coffee supply chain with a fuzzy approach. Identification and mitigation of upstream to downstream risks are needed to achieve the objectives of the organic coffee supply chain in Pasrujambe District, Lumajang Regency. Supply chain risk identification is carried out using the Fuzzy Failure Mode and Effect Analysis (FFMEA) method and determining risk mitigation strategies using the Fuzzy Analytic Hierarchy Process (FAHP) method. Both methods use expert respondents consisting of 3 farmers, 3 large collectors, and 3 experts in roastery. The results of the identification of the highest supply chain risk at the farmer level are the risk of non-uniform coffee fruit size (5.74), at the large collector level is price fluctuation (4.79), and at the roastery, the level the failure to regulate roasting temperature and time with an fuzzy risk priority number (FRPN) value of 5,26. Therefore, to minimize and mitigate these priority risks at the farmer level, increasing knowledge about organic coffee cultivation is necessary. At the large collector level, it is necessary to build institutional internalization stability, and at the roastery level, to improve the quality of the roastmaster.